Online Resources for People Who Self-Harm and Those Involved in Their Informal and Formal Care: Observational Study with Content Analysis - Daniel Romeu (International Journal of Environmental Research and Public Health, 2020)
Despite recent fears about online influences on self-harm, the internet has potential to be a useful resource, and people who self-harm commonly use it to seek advice and support. Our aim was to identify and describe UK-generated internet resources for people who self-harm, their friends or families, in an observational study of information available to people who search the internet for help and guidance. The different types of advice from different websites were grouped according to thematic analysis. We found a large amount of advice and guidance regarding the management of self-harm. The most detailed and practical advice, however, was limited to a small number of non-statutory sites. A lay person or health professional who searches the web may have to search through many different websites to find practical help. Our findings therefore provide a useful starting point for clinicians who wish to provide some guidance for their patients about internet use. Websites change over time and the internet is in constant flux, so the websites that we identified would need to be reviewed before making any recommendations to patients or their families or friends.